International Relations and HRD Activities of the International Nuclear Nonproliferation and Security Academy of the ROK - Kwan Kyoo Choe (International Journal of Nuclear Security, 2015)
The objective of this article is to explain the HRD activities on nuclear nonproliferation and security area of the International Nuclear Nonproliferation and Security Academy (INSA) of the Korea Institute of Nuclear Nonproliferation and Control (KINAC). The HRD activities on nuclear security in international society have moved gradually from military dimension to the aspect of social management of conflict and threat. The paper would be developed in the following ways; First, the main concept of nuclear security in the Republic of Korea(ROK) will be touched, which could show us why and how the ROK has put its step forward into the HRD efforts. Second, the background in conjunction with international relations and its developing process how the Korea Center of Excellence (COE), named as INSA, had been set would be described. Third, the detailed efforts of the ROK to build a COE in Korea in connection with the 2nd Nuclear Security Summit (NSS) will be touched with a detailed explanation on its main activities, direction and the perspective. Finally, the aspect of nuclear culture issues and lessons learned in the first year of the nuclear nonproliferation and security HRD activities of the INSA would be developed.
Keywords: HRD; Nuclear Nonproliferation; Nuclear Security; Korea; KINAC; INSA; COE; Nuclear Material; Terrorism; Best Practice; NSS; SAT; SETT